2021
DOI: 10.30598/arika.2021.15.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Strategy to Improve the Class of Ambon Archipelago Fisheries Port Into an Ocean Fishery Port Using Swot Analysis

Abstract: An essential factor for the development of fisheries business, especially fishing activities, is the availability of infrastructure for berths or shelter for fishing vessels and landing their catch fish. The infrastructure is in the form of a Fishing Port or Fish Landing Base as a place or base for fishing vessels. This research aimed to examine the condition of Archipelago Fisheries Port (AFP) on the criteria of an Ocean Fishery Port (OFP), and formulated a strategy for developing Ambon AFP in order to increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
0
5
0
2
Order By: Relevance
“…Apart from being the primary source of livelihood, the number of fishers at PPI Binuangeun is in line with the increase in the fleet and fishing gear in PPI Binuangeun. Research by Pamungkas et al (2019); Wahyuni and Kandi (2019); Ariwibowo (2020); Soumokil (2021) revealed that the high production capacity of fish caught by fishers must be supported by adequate fleets and tools and supportive capacity in terms of quantity and quality. The better the fleet and fishing gear are used and supported by adequate resources, the more the number of catches increases (Fujii 2021; Selig et al 2022).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Apart from being the primary source of livelihood, the number of fishers at PPI Binuangeun is in line with the increase in the fleet and fishing gear in PPI Binuangeun. Research by Pamungkas et al (2019); Wahyuni and Kandi (2019); Ariwibowo (2020); Soumokil (2021) revealed that the high production capacity of fish caught by fishers must be supported by adequate fleets and tools and supportive capacity in terms of quantity and quality. The better the fleet and fishing gear are used and supported by adequate resources, the more the number of catches increases (Fujii 2021; Selig et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The interview results showed that 86.95% of fishers strongly agree that the PPI Binuangeun class is increased, and as many as 13.04% others do not agree and feel that it is sufficient so that it does not need to be increased by assuming it will harm small fishers. According to fishers, if the class increase is carried out, it will make the fishing port bigger so that it becomes an entry point for large ships and impacts small fishers, including their income (Pamungkas et al 2019;Wahyuni and Kandi 2019;Ariwibowo 2020;Soumokil 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pemanfaatan sumberdaya ikan di Kabupaten Wakatobi memerlukan infrastruktur pelabuhan perikanan. Pelabuhan perikanan dimaksudkan menjadi sentra produksi dan perdagangan perikanan yang dapat menjadi penggerak utama perekonomian di suatu kawasan (Soumokil 2021). Pelabuhan perikanan berperan sebagai basis utama kegiatan industri perikanan, pusat interaksi nelayan dengan pemerintah daerah, dan sebagai pendorong aktivitas usaha pemanfaatan sumberdaya perikanan secara optimal dan berkelanjutan (Tahir et al 2020).…”
unclassified